Acoustic scattering layers reveal a faunal connection across the Fram Strait - Gjøsæter, Harald; Ingvaldsen, Randi Brunvær; Christiansen, Jørgen Schou (Progress in Oceanography, 2020)
Acoustic scattering layers (SL) at various depths are common phenomena in most oceans, but the organisms that make up these layers vary and so does their density, and hence the backscattered energy. During two crossings of the deep Fram Strait between the shelves at Svalbard and Northeast Greenland at latitudes 77°N and 79°N, we registered epipelagic and mesopelagic SL across the entire Fram Strait and quantified their acoustic backscattered energy. In addition, one pelagic trawl haul was made at each crossing together with a CTD cast at the northern crossing. The epipelagic SL was present at 0–200 m depth, whereas the mesopelagic SL was located at 300–500 m depth during day and at shallower depths during night indicating diel vertical migrations. The epipelagic SL consisted of young-of-the-year fishes, mostly redfish Sebastes sp. No trawl hauls were made in the mesopelagic SL, and the identity of organisms is unknown. Few strong echoes from single targets at mesopelagic depths stood out from the rest of the targets and were interpreted as adult Atlantic cod Gadus morhua . This is the first report of scattering layers covering the whole distance of the deep parts of the Fram Strait, and strengthen the assumption about an east–west connection of organisms and young-of-the-year fishes originating from the spawning grounds along the Norwegian coast and the western Barents Sea towards Northeast Greenland.